An assessment of construction delay management: A Nepalese perspective - Giri, Om Prakash; Pahari, Anuska; Lamichhane, Basu Dev (Edelweiss Applied Science and Technology, 2025)
Delays are a significant issue in the global construction industry, and Nepal is no exception. Both private and government construction projects in Nepal face delays, leading to cost overruns, disputes, and compromised project outcomes. This research explores the causes, impacts, and mitigation strategies of delays in private residential construction projects in Pokhara Valley. This research utilizes a mixed-methods approach, combining primary data through questionnaires distributed to contractors, consultants, and project stakeholders in Pokhara Valley, and secondary data from the Pokhara Metropolitan City. The study categorizes delay factors into Production, Internal, and External environments, analyzed using the Relative Importance Index (RII). The major findings include socio-economic, regulatory, environmental, and technical issues such as poor planning, labor shortages, bureaucratic hurdles, weather challenges, and supply chain disruptions, leading to multifaceted project delays. Delays in private residential construction projects in Pokhara Valley significantly impact developers, contractors, homeowners, and the community, causing increased costs, missed deadlines, reduced investor confidence, and hindering regional development. To address these issues, this research proposes tailored mitigation strategies, including proactive project planning, strengthened stakeholder collaboration, improved regulatory frameworks, investment in workforce skills, and the adoption of innovative construction technologies. These solutions aim to enhance efficiency, minimize delays, and promote sustainable growth in Pokhara Valley’s construction sector. This research offers practical insights to improve construction project management by minimizing delays, reducing costs, and enhancing efficiency. It aids stakeholders in fostering collaboration, compliance, and innovation, supporting sustainable growth in Pokhara Valley and similar contexts in developing countries.